Family conferences and shared prioritisation to improve patient safety in the frail elderly (COFRAIL): study protocol of a cluster randomised intervention trial in primary care. - Mortsiefer, Achim; Wilm, Stefan; Santos, Sara; Loescher, Susanne; Wollny, Anja; Drewelow, Eva; Ritzke, Manuela; Thuermann, Petra; Mann, Nina-Kristin; Meyer, Gabriele; Abraham, Jens; Icks, Andrea; et al. (Trials, 2020)
Frailty in elderly patients is associated with an increased risk of poor health outcomes, including falls, delirium, malnutrition, hospitalisation, and mortality. Because polypharmacy is recognised as a possible major contributor to the pathogenesis of geriatric frailty, reducing inappropriate medication exposure is supposed to be a promising approach to improve health-related quality of life and prevent adverse outcomes. A major challenge for the process of deprescribing of inappropriate polypharmacy is to improve the communication between general practitioner (GPs), patient and family carer. This study investigates the effects of a complex intervention in frail elderly patients with polypharmacy living at home.This is a cluster randomised controlled trial including 136 GPs and 676 patients. Patients with a positive clinical screening for frailty are eligible if they are aged 70 years or older, receiving family or professional nursing care at home, and taking in five or more drugs per day. Exclusion criteria are higher grade of dementia and life expectancy of 6 months or less. The GPs of the intervention group receive an educational training promoting a deprescribing guideline and providing information on how to conduct a family conference focussing on prioritisation of treatment goals concerning drug therapy. During the 1-year intervention, GPs are expected to perform a total of three family conferences, each including a structured medication review with patients and their family carers. GPs of the control group will receive no training and will deliver care as usual. Geriatric assessment of all patients will be performed by study nurses during home visits at baseline and after 6 and 12 months. The primary outcome is the hospitalisation rate during the observation period of 12 months. Secondary outcomes are number and appropriateness of medications, mobility, weakness, cognition, depressive disorder, health-related quality of life, activities of daily living, weight, and costs of health care use.This study will provide evidence for a pragmatic co-operative and patient-centred educational intervention using family conferences to improve patient safety in frail elderly patients with polypharmacy.German Clinical Trials Register, DRKS00015055 (WHO International Clinical Trials Registry Platform [ICTRP]). Registered on 6 February 2019.
EVALuna2:279912